Outcome following subdural haemorrhages in infancy. Issue 4 (21st March 2007) - Jayawant, Sandeep; Parr, Jeremy
Abstract : Subdural haemorrhages (SDH) are associated with significant neurodisability in affected individuals. The incidence of SDH in infants is between 12 and 25 cases per 100 000 children and most detected SDH are due to physical abuse. In the infant brain, SDH are caused by tearing of the bridging veins in the subdural space and may result in significant brain injury. The challenge of assessing outcome in infants with SDH is evaluating whether SDH or other accompanying brain insults are instrumental in the neurodevelopmental outcome.